Argumentação na língua: análise polifônica em notícias online - Santos, Girlene Lobo dos (2017)
In this dissertation, we make a semantic argumentative analysis, is done from the meanings guided for implicit and operators - as index of argumentativity and polyphony in online news. To that end, we chosen news that deals with the same fact: the Datafolha results about on the evaluation of the government of President Dilma Rousseff published on February 7, 2015. The reported fact refers to the low popularity of the petista - linked to the Workers' Party (PT) - and the political situations that triggered this drop. We highlight a corpus that is limited to three news items, taken from three different online midias. According to the principles of Theory Argumentative Semantic, from Oswald Ducrot's (1987), we analyze the news in order to perceive polyphony in the journalists' discourses and, therefore, to capture the argumentative orientation in the news. The results point to the conclusion that the same fact may have different meaning depending on the media which relays and the objective of the communicative reporter. To for this kind of meaning, the argumentative operators and the implicit act as devices that indicate the voices of other enunciators in the news and reveal the saying assumed by the journalist.